2007
DOI: 10.2139/ssrn.997963
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Judicial Ideology in Intellectual Property Cases

Abstract: This article investigates the relationship between ideology and judicial decision-making in the context of intellectual property. This article empirically establishes that judicial decision making in relation to IP is significantly and predictably shaped by judicial ideology. Using data drawn from Supreme Court intellectual property cases decided in between 1954 and 2006, we show that ideology is a significant determinant of cases involving intellectual property rights. However, our analysis also shows that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…In addition, we have shown that there is an underlying ideological component to decisionmaking in obviousness cases—and that the effect of ideological considerations is partially contingent upon expertise. This supports and extends the assertions of others (Sag et al 2009; Howard 2005) in showing that otherwise complex or technical areas of law are not immune to ideological decisionmaking.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In addition, we have shown that there is an underlying ideological component to decisionmaking in obviousness cases—and that the effect of ideological considerations is partially contingent upon expertise. This supports and extends the assertions of others (Sag et al 2009; Howard 2005) in showing that otherwise complex or technical areas of law are not immune to ideological decisionmaking.…”
Section: Discussionsupporting
confidence: 87%
“…As part of that analysis, we also consider how such expertise may interact with ideological considerations to affect judicial decisionmaking. Ultimately, we extend the work of others (Sag et al 2009; Howard 2005) by showing that decisionmaking in patent cases, as in some other technical areas of law, can be ideological.…”
supporting
confidence: 60%
See 2 more Smart Citations
“…In any event, in order to accurately assess the possible pertinence of ideological considerations to the Federal Circuit's decisions in obviousness cases, in addition to any interactive effect ideological factors may have with expertise, we must necessarily define liberal and conservative outcomes in patent obviousness cases. As has been noted elsewhere (Sag, Jacobi, and Stych 2007;Miller and Curry 2009), simply relying on the underdog/upperdog distinction that often governs the coding of economic case data is inappropriate for examining obviousness decisions. 11 Consequently, we utilize traditional economic stances of Republicans and Democrats to conceptualize the ideological outcomes in patent obviousness cases.…”
Section: The Potential Relevance Of Ideologymentioning
confidence: 99%